Mitochondrial defects and oxidative stress in Alzheimer disease and Parkinson disease - Yan, Michael H.; Wang, Xinglong; Zhu, Xiongwei (Free radical biology & medicine, 2013)
Alzheimer disease (AD) and Parkinson disease (PD) are the two most common age-related neurodegenerative diseases characterized by prominent neurodegeneration in selective neural systems. Although a small fraction of AD and PD cases exhibit evidence of heritability, among which many genes have been identified, the majority are sporadic without known causes. Molecular mechanisms underlying neurodegeneration and pathogenesis of these diseases remain elusive. Convincing evidence demonstrates oxidative stress as a prominent feature in AD and PD and links oxidative stress to the development of neuronal death and neural dysfunction, which suggests a key pathogenic role for oxidative stress in both AD and PD. Notably, mitochondrial dysfunction is also a prominent feature in these diseases, which is likely to be of critical importance in the genesis and amplification of reactive oxygen species and the pathophysiology of these diseases. In this review, we focus on changes in mitochondrial DNA and mitochondrial dynamics, two aspects critical to the maintenance of mitochondrial homeostasis and function, in relationship with oxidative stress in the pathogenesis of AD and PD. [Display omitted] ► This review focuses on mtDNA and mitochondrial dynamics as target and mediator of oxidative stress. ► Alterations in mtDNA and mitochondrial dynamics in Alzheimer disease are discussed. ► Alterations in mtDNA and mitochondrial dynamics in Parkinson disease are also discussed.